THE DEVELOPMENT OF LEGAL SYSTEM IN INDONESIA THAT BASED ON THE VALUE PANCASILA - Aristo Evandy A. Barlian (Universitas Muhammadiyah Metro, 2017)
Indonesia is a plural or pluralistic society, which includes a variety of awareness both personal and group. In the development of the legal system in Indonesia, which became an important part of cultural and community awareness is very influential in the development. Indonesia is a culture and awareness of the law is no single or uniform, although in principle there are various similarities in the pluralistic society. Existing equation should be used to formulate a legal union, although many different cultures in Indonesia. Pancasila is the philosophical basis for the formation of the unitary state of Indonesia, therefore, for the realization of national unity in enacting a national law in Indonesia must be based on Pancasila and the 1945 Constitution as the supreme norm. The objective of this study will clarify that the law enacted at this time still does not reflect the values of Pancasila and impressed liberalism, as the law is currently drafted and enforced on the basis of normative thinking less backed up to a statement of the case and the plural society , namely empirical thinking. Methodology This study will explain the values of Pancasila and culture in the development of legislation that affects the development of the other, which can be reviewed comprehensively in this paper. Thus for the sake of the welfare of the nation and public awareness of the law, the results of this study will explain the need for the development of legal systems that systemic and continuously keeping with the character of the Indonesian nation, namely the development of legislation based on the Pancasila.